KESALAHAN BERBAHASA PADA KARANGAN GURU BAHASA INDONESIA SMP SELAMPUNG UTARA - Kiki Zakiah Nur (TELAGA BAHASA, 2017)
The problems discussed in this study is language errors in the essays ofIndonesian language teacher of junior high school in Kotabumi, LampungUtara. This study aimed to describe teachers' language errors in spelling,diction, morphology, and sentences. The method used in this research was descriptive which means that data sources are in the form of the teacher’s essays. From the analysis the spelling errors that can be identified is the punctuation errors include the use of comma, colon, semicolon, quotation, single quote, and hyphen; the errors on writing include the use of capital letters, foreign language element, numbers, and word combination. Diction errors include the use of non-standard words and words that inappropriate. Morphology errors include the use of the incorrect word formation and the words are not in accordance with a sentence. The errors on the use of sentence include a mismatch, the vagueness of subject and predicate, the absence of a subject, predicate, and object in the sentence, and the sentence which only has a caption, the use of coordinator and subordinator conjunction at the beginning of single sentence, and incoherence.